An energy-efficient glass using biomimetic structures with excellent energy saving features in both hot and cold weather. (August 2022) - Wang, Fuqiang; Zhang, Xinping; Wang, Haoran; Li, Yang; Dong, Yan; Lin, Bo; Liang, Huaxu; Cheng, Ziming
Highlights: Idea of using biomimetic structures to control solar irradiation was proposed. The optical performance of energy-efficient glass was examined using FDTD method. The τ e = ∼ 82 % and ρ N I R = ∼ 90 % of energy-efficient glass were higher than that of low-E glass. Energy-efficient glass could save about 20% total electrical consumption per year. Abstract: Solar irradiation is the main factor contributing to ultra-high energy demand in buildings, and windows are crucial elements with a significant effect on the energy demand in indoor spaces, affecting the cooling, heating, and artificial lighting requirements. Inspired by hercules beetle utilizing the refractive index difference of spongy multilayer structure for infrared reflection and moth-eye using the continuous refractive index change of microscopic convex structure for anti-reflection, this study proposes a visibly transparent and infrared-reflective energy-efficient glass using biomimetic structures to save energy in buildings, based on the idea of regulating the radiation to match the energy utilization on-demand. The selected materials for the proposed biomimetic energy-efficient (BE) glass are SiO2, Al2 O3, and Ag based on the idea of using the difference in refractive index of multilayer media for radiation regulating. The transmissivity and reflectivity of BE glass are examined adopting the finite-difference time-domain (FDTD) method. The numerical analysis results demonstrate that BE glass covered with a cone-shaped biomimetic moth-eye structure and a biomimetic multilayer structure exhibits visible light transmissivity of 82.37%, in addition to an infrared light reflectivity of over 90%, which is higher than that of the currently employed low-E glasses. The proposed BE glass offers excellent energy-saving features in both hot and cold weather and the energy consumption analysis indicates that comparing with conventional common glass, it could save about 20% total electrical consumption (43.5 kWh/m 2 ) per year Graphical abstract: Image, graphical abstract